Ghrelin gene polymorphisms in rheumatoid arthritis - Ozgen, Metin; Koca, Suleyman Serdar; Etem, Ebru Onalan; Yuce, Huseyin; Aydin, Suleyman; Isik, Ahmet (Elsevier France-Editions Scientifiques Medicales Elsevier, 2011)
Objectives: Ghrelin, an endogenous orexigenic peptide, has anti-inflammatory effects, down-regulates pro-inflammatory cytokines, and its altered levels are reported in various inflammatory diseases. The human preproghrelin (ghrelin/obestatin) gene shows several single nucleotide polymorphisms (SNPs) including Arg51Gln, Leu72Met, Gln90Leu, and A-501C. The aim of this study was to investigate the frequency, and clinical significance, of these four SNPs in a small cohort of Turkish patients with rheumatoid arthritis (RA). Methods: The study included 103 patients with RA and 103 healthy controls. In the RA group, disease activity and disease-related damage were assessed using the Disease Activity Score-28 (DAS-28), and the modified Larsen scoring (MLS) methods. In all the participants, genomic DNA was isolated and genotyped by polymerase chain reaction and restriction fragment length polymorphism analysis. Results: The frequencies of ghrelin gene SNPs were 82.5 and 79.6% in the RA and control groups, respectively, and there were no significant differences in terms of genotype distributions and allele frequencies for these four SNPs between the groups. However, the A-501C SNP was found to be associated with early disease onset, and Gln90Leu SNP with less frequent rheumatoid factor positivity, in the RA group. Conclusion: A-501C SNP is associated with earlier onset of RA suggesting that genetic variations in the ghrelin gene may have an impact on RA. (C) 2010 Societe francaise de rhumatologie. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Ghrelin gene polymorphisms; Inflammation; Rheumatoid arthritis